PENGEMBANGAN SISTEM INFORMASI BERBASIS WEBSITE PADA PROGRAM STUDI S3 PENDIDIKAN VOKASI KETEKNIKAN DI PROGRAM PASCASARJANA UNIVERSITAS NEGERI MAKASSAR - Indah Melisa; Purnamawati; Abdul Muis Mappalotteng (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
This study aims to: a) Design a website-based information system for the PPs UNM Engineering Vocational Education Doctoral Program, and b) produce a website-based information system that is Practically Valid and Effective in the PPs UNM Vocational Engineering Vocational Education Doctoral Study Program. The method used in this research is Research and Development (R&D). The procedure of this research adapts the ADDIE development model which consists of five stages which include Analysis, Design, Development, Implementation and Evaluation (Evaluation). The results of this study obtained a Website-based Information System to be applied in the PVKT Doctoral Program at the Makassar State University Postgraduate Program and there are main menus, namely, Home, Profile, Lecturer, Academic, Alumni News, and Engineering Vocational Journal. The results of the validity testing carried out by 2 design expert validators showed that the website-based information system developed was included in the very valid category (very feasible) and the results of the respondent's trial were stated to be very feasible, from the results of the research on the websitebased information system that was developed the category